PENDEKATAN BIMBINGAN KONSELING KRISTEN DALAM MEMBANGUN HUBUNGAN KELUARGA YANG HARMONIS - Delviyanti; Jesklin Musa; Femi; Julia Lepong Bulan; Feronika Salembe' (ADIBA : JOURNAL OF EDUCATION, 2024)
This research aims to explore the role and impact of the Christian counseling approach in building harmonious family relationships. By integrating Christian values such as love, forgiveness, effective communication, and peaceful conflict resolution, this approach provides a solid framework for Christian families to enhance the quality of their relationships. The research method used is a literature review analysis, examining literature related to Christian counseling theory and family dynamics. The research findings indicate that the Christian counseling approach has a significant positive impact on strengthening the emotional and spiritual bonds among family members. Integrating Christian values into the counseling process enables families to understand and resolve conflicts in accordance with Christian teachings, as well as to build healthier and more meaningful communication. These research results have important implications for family counseling practice, highlighting the importance of considering the spiritual dimension in understanding and supporting the growth of harmonious families.